Distribution of Recent non-marine ostracods in Icelandic lakes, springs, and cave pools. Issue 3 (25th April 2019) - Alkalaj, Jovana; Hrafnsdottir, Thora; Ingimarsson, Finnur; Smith, Robin J; Kreiling, Agnes-Katharina; Mischke, Steffen
Abstract: Ostracods in Icelandic freshwaters have seldom been researched, with the most comprehensive record from the 1930s. There is a need to update our knowledge of the distribution of ostracods in Iceland as they are an important link in these ecosystems as well as good candidates for biomonitoring. We analysed 25, 005 ostracods from 44 lakes, 14 springs, and 10 cave pools. A total of 16 taxa were found, of which seven are new to Iceland. Candona candida (Müller, 1776 ) is the most widespread species, whereas Cytherissa lacustris (Sars, 1863 ) and Cypria ophtalmica (Jurine, 1820 ) are the most abundant, showing great numbers in lakes. Potamocypris fulva (Brady, 1868 ) is the dominant species in springs. While the fauna of lakes and springs are relatively distinct from each other, cave pools host species that are common in both lakes and springs. Icelandic non-marine ostracods include mostly generalist species, as well as species adapted to cold climates and resemble those of other north European countries while sharing very few species with the North American Arctic. Iceland is experiencing impacts from climate change and a booming tourism. It is possible to use selected freshwater ostracods as biomonitoring tools by constructing a detailed database of these species.